Comparisons of Serum Interleukin-8 Levels in Major Depressive Patients With Drug-Free Versus SSRIs Versus Healthy Controls - Zhu, Zhen Hua; Song, Xiao Ying; Man, Li Juan; Chen, Peng; Tang, Zhen; Li, Rong Hua; Ji, Cai Fang; Dai, Ning Bin; Liu, Fang; Wang, Jing; Zhang, Jianping; Jia, Qiu Fang; et al. (Frontiers in Psychiatry, 2022)
Objective: The interleukin-8 (IL-8) has been reported to play an important role in depression, which might be modulated by the selective serotonin reuptake inhibitors (SSRIs). Thus, the aim of this study was to investigate serum IL-8 levels, depressive symptom, and their associations in drug-free MDD patients, MDD patients with SSRIs, and healthy controls (HCs). Methods: Fifty-seven drug-free MDD patients (male/female = 35/22, mean age: 39.24 years), 30 MDD patients with SSRIs (male/female = 11/19, mean age: 39.73 years), and 101 HCs (male/female = 52/49, mean age: 37.38 years) were recruited in this cross-sectional study. Serum IL-8 levels and depressive symptom were assessed using the Flow Cytometer and Hamilton Depression Scale (HAMD). The analysis of variance was used for the comparison between groups. The relationship between serum log10 IL-8 levels and HAMD score was analyzed by Pearson correlation. Results: Serum log10IL-8 levels were lower in all patients than HCs after controlling for covariates (F = 4.86, p = 0.03). There was significant difference in serum Log10IL-8 levels among three groups after controlling for covariates (F = 14.63, p < 0.001). Serum Log10IL-8 levels in drug-free patients were lower compared to HCs (F = 19.38, p < 0.001) or patients with SSRIs (F = 21.89, p < 0.001) after controlling for covariates. However, there was not difference in serum log10IL-8 levels between patients with SSRIs and HCs after controlling for covariates. Moreover, serum Log10IL-8 levels were negatively correlated with HAMD score in all patients (r = -0.37, p = 0.02). Also, serum Log10IL-8 levels were negatively correlated with HAMD score in drug-free patients (r = -0.74, p = 0.01), but not in patients with SSRIs. Conclusion: Our data supported that the decline in serum IL-8 levels was association with depression. Moreover, the SSRIs might modulate increased serum IL-8 levels of depression.